Machine Learning Applications in Seismology (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The purpose of this Special Issue is to immerse readers in the transformative impact of machine learning-based artificial intelligence on seismology. From digital seismic data processing to the development of structured seismic catalogs, AI technology is poised to revolutionize our understanding of earthquakes. By enabling multiple geophysical observations, AI uncovers signals and patterns that traditional methods overlook, offering new insights into the physical processes of earthquakes. In this Special Issue, leading experts share their innovative ideas and latest findings in earthquake monitoring, early warning, and forecasting systems, all developed through cutting-edge machine learning methods, theories, and applications. Together, we explore the potential of AI in seismology, aiming to enhance our ability to predict and understand seismic events. This journey promises to advance our scientific knowledge and improve our preparedness for future earthquakes, paving the way for a safer and more informed world.